Imobilização de frutosiltransferase extracelular de Aspergillus oryzae IPT-301 em bagaço de cana-de-açúcar para a produção de fruto-oligossacarídeos - Rocha, Rovilson José Da (2021)
Fructooligosaccharides (FOS) are low-calorie nutraceutical sugars that have excellent functional properties and benefits for human health and nutrition. Industrially, FOS can be obtained by the transfructosylation reaction of sucrose molecules, catalyzed by microbial enzymes such as fructosyltransferase (FTase, EC 2.4.1.9). The use of soluble FTase implies low stability (thermal, operational, storage and pH), however, with immobilization, it is possible to increase the stability of the enzyme and enable its recovery and reuse. In this work, the physical characterization of in natura sugarcane bagasse was carried out (specific area - BET; pore volume and distribution - BJH), immobilization by physical adsorption (35 ºC, 175 rpm, pH 5.5 and 8 h) extracellular FTase from Aspergillus oryzae IPT-301 in in natura sugarcane bagasse and obtaining immobilization parameters (yield and recovered activity). Then, the characterization (FTIR) of the enzyme-support derivative obtained from the immobilization process and the evaluation of its biochemical properties was carried out, which involved: the evaluation of the influence of temperature and pH on the transfructosylation activity – experimental design; evaluation of the influence of substrate concentration on transfructosylation activity; stability tests (thermal, compared to incubation, operational and storage pH). Through the physical characterization of in natura sugarcane bagasse, a specific area of 1.306 m².g-1, a specific pore area of 0.846 m².g-1, a pore size of 20.408 Å and a specific volume of pores (between 17 and 3000 Å) of 0.431×10-3 cm³.g-1. The immobilization yield was 46.61 ± 3.77 % and the recovered activity was 11.20 ± 1.85 %. Comparative analysis of enzyme-support and support derivatives by FTIR indicated enzymatic immobilization. The results of the design of experiments indicated that at a temperature of 51.37 ºC and pH of 5.49, the enzymatic activity of immobilized FTase was maximum. The best sucrose concentration for the enzymatic reaction was 600 g.L-1 and the Michaelis-Menten and Hill kinetic models were satisfactorily fitted to the experimental data. The stability tests against the incubation pH showed that FTase was stable (relative activities above 56 %) in the pH range between 4.5 and 8.5. The thermal stability tests showed that immobilization increased the thermostability of FTase, with a maximum stability factor of 3.47 at 30 ºC, which represents a gain of about 9 h in the half-life of the enzyme. The analysis of associated thermodynamic parameters also indicated that enzymatic thermostability was increased after immobilization. Operational stability assays showed that the enzyme can be reused for 2 consecutive reaction cycles without loss of activity. The enzyme-support derivative showed no loss of enzymatic activity in the first 5 days of storage (retained activities close to 100 %), however, after 10 and 15 days of storage, transfructosylation activities equivalent to 87 % and 74 % of the initial activity were obtained, respectively. After 30 days of storage, the enzyme-support derivative retained only 17 % of the initial enzyme activity. It was concluded that the immobilization of FTase in sugarcane bagasse was satisfactory, by obtaining a stable and active biocatalyst, which justifies the future implementation in different reactor configurations.